2009
DOI: 10.1007/s10689-009-9284-2
|View full text |Cite
|
Sign up to set email alerts
|

p53 tetramerization domain mutations: germline R342X and R342P, and somatic R337G identified in pediatric patients with Li–Fraumeni syndrome and a child with adrenocortical carcinoma

Abstract: Germline p53 mutations are associated with Li-Fraumeni syndrome (LFS) and other familial cancer phenotypes not fulfilling the definition for LFS. The majority of germline p53 mutations cluster in exons 5-8, corresponding to a DNA binding domain. We report the identification of two germline mutations and a somatic mutation in a tetramerization domain (TD), a rare site for mutations. The germline mutation, R342X (16915C>T), and the novel mutation, R342P (16916G>C), were found in a child with adrenocortical carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…For example, tetramerization of p53 is essential for its binding to DNA . Mutations in the p53 tetramerization domain have been reported in patients with Li–Fraumeni syndrome, a rare disease presented as early cancer onset …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, tetramerization of p53 is essential for its binding to DNA . Mutations in the p53 tetramerization domain have been reported in patients with Li–Fraumeni syndrome, a rare disease presented as early cancer onset …”
Section: Discussionmentioning
confidence: 99%
“…39 Mutations in the p53 tetramerization domain have been reported in patients with Li-Fraumeni syndrome, a rare disease presented as early cancer onset. 40 MPZL3 (myelin protein zero-like 3) acts downstream of several known transcriptional regulators, including p63. It is essential for normal epidermal differentiation.…”
Section: Cancer Genetics and Epigeneticsmentioning
confidence: 99%
“…In this family pediatric neoplasms occurred, namely a synovial sarcoma at the age of 8 and an osteosarcoma at 12 years of age in one individual. In the study of Fiszer-Maliszewska et al [16] it was assumed that the p.Arg342Pro mutation was causally related to the Li-Fraumeni phenotype, but co-segregation of mutation and disease could not be shown because of lack of family members available for testing. In our study, we succeeded to extract and analyze old genomic DNA from a blood typing bedside test of the index patient's mother who had died 29 years ago of bilateral breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These mutations hit the DNAbinding domain (DBD). Meanwhile, however, several in vitro studies [12][13][14][15] and some clinical reports [16][17][18] have also shown that mutations in the tetramerization domain (TD) of p53 may have a destructive effect on protein functionality and are of pathological relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Essa síndrome familiar parece estar associada principalmente a mutações germinativas no gene TP53 em 70% dos pacientes (46). Diversas mutações neste gene, incluindo as mutações p.R342X, p.R342P e p.R337G, também foram encontradas em crianças com TAC associadas à síndrome de Li-Fraumeni (47).…”
Section: Bases Moleculares Dos Tumores Adrenocorticaisunclassified